The Cost-Based Lean Approach to the Information Logistics Business System Modelling - Robert Bucki; Petr Suchanek (Journal of Computing and Information Technology, 2019)
The paper highlights the problems of modelling the complex logistics manufacturing system which is to meet the needs of the contemporary lean approach to manufacturing. It is assumed that the system consists of identically arranged and equipped subsystems, however, each of them is characterised by different operating and fixed costs. The software engineering method used to create the simulator of the discussed system is emphasised to show how the necessary assumptions turn the real manufacturing system into the mathematical model of the logistic-business system, and subsequently into the simulator. Manufacturing strategies as well as heuristic algorithms are introduced in order to control making the order. The case study presents the method of searching for the most adequate manufacturing subsystem for making the order on the basis of cost calculation. The key points responsible for excessive costs are detected. A thorough analysis based on modified operating as well as fixed costs is carried out.